SSA challenge program: Lake kivu pilot learning site : Projected workplans and budgets for 2011-2012 - Nyamwaro, Sospeter S.; Buruchara, Robin Arani (International Center for Tropical Agriculture, 2010)
Project Work plans & Budgets for 211-2012 Presented at the Cross-Site Regional Review & WriteshopMeeting of LKPLS, November 08-12, 2010, Kigali, Rwanda